Positive electrode material and battery

By using lithium nickel-cobaltate composite oxides in high-nickel positive electrode materials and optimizing the cladding structure and grain size, problems such as cationic mixed discharge and surface alkali residues are solved, and low gas production, low impedance and high safety performance are achieved the positive electrode material.

CN119419228APending Publication Date: 2025-02-11BTR (JIANGSU) NEW MATERIAL TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411354624.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

In power battery applications, high-nickel positive electrode materials have problems such as cationic mixed discharge, surface alkali residue, gas production, increased impedance, poor rate performance, and poor cycle stability, which limits its further application in the market.

Method used

The lithium nickel-cobaltate-based composite oxide is used as the positive electrode material, and the coating structure and grain size of the material are optimized through the potential titration test and the XRD diffractometer test to improve the structural order and stability of the material.

Benefits of technology

It effectively reduces the gas production and impedance of the cathode material, improves the stability and electrochemical properties of the structure, and enhances safety and cycling properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419228A_ABST
    Figure CN119419228A_ABST
Patent Text Reader

Abstract

The invention relates to a positive electrode material and a battery. The positive electrode material is a lithium nickel cobalt oxide composite oxide. The positive electrode material comprises a base material and a coating layer on at least part of the surface of the base material; performing an acid-base potentiometric titration test on the positive electrode material by using a potentiometric titrator and hydrochloric acid with a concentration of 0.02 mol / L to obtain a curve graph of a relationship between a differential value dpH / dV and a consumption volume VmL of hydrochloric acid, the dpH / dV being a differential value obtained by differentiating the consumption volume VmL of hydrochloric acid by using a pH value; in a relation curve graph of the differential value dpH / dV and the consumption volume VmL of the hydrochloric acid, the positive electrode material has a first characteristic peak when the consumption volume of the hydrochloric acid is V1mL, the positive electrode material has a last characteristic peak when the consumption volume of the hydrochloric acid is V2mL, and V1 and V2 meet the relation: 0.6 < V2-V1 < 2.7. According to the positive electrode material, gas production and impedance of the positive electrode material can be reduced, and meanwhile, the structural orderliness and structural stability of the positive electrode material are improved, so that the safety performance, the capacity and the cycle performance of the positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials and batteries. Background Art

[0002] Lithium-ion batteries have the advantages of high operating voltage, long cycle life, wide application range, low environmental pollution and no memory effect, so they are widely used in portable electronic devices. As the core component of lithium-ion batteries, the performance of positive electrode materials directly determines the overall performance of the battery. Therefore, the development of positive electrode materials with excellent performance has always been a research hotspot. Among a series of positive electrode materials, layered high-nickel ternary materials LiNi x CO y MnO2 (NCM, x≥0.8, x+y+z=1) is considered to be the most promising cathode material in the field of power batteries due to its advantages such as high specific capacity and high voltage platform. However, with the continuous increase in nickel content, high nickel cathode materials have serious problems such as cation mixing, surface residual alkali, gas production, increased impedance, poor rate performance, and poor cycle stability, which limits its further application in the power battery market.

[0003] At present, the conventional technical means to improve the above problems are mainly doping and coating, but the existing modification methods such as doping and coating are complicated and have high process costs, and the improvement effect on the above problems is limited, and cannot simultaneously meet the requirements for improving the electrochemical properties and safety performance of the positive electrode materials. Summary of the invention

[0004] The present application provides a positive electrode material and a battery. The positive electrode material of the present application can reduce the gas generation and impedance of the positive electrode material, while improving the structural orderliness and structural stability of the positive electrode material, thereby improving the safety performance, capacity and cycle performance of the positive electrode material.

[0005] In a first aspect, the present application provides a positive electrode material, wherein the positive electrode material is a nickel cobalt lithium oxide composite oxide; the positive electrode material comprises a base material and a coating layer located on at least a portion of the surface of the base material;

[0006] The positive electrode material is subjected to an acid-base potentiometric titration test using a potentiometric titrator and hydrochloric acid with a concentration of 0.02 mol / L to obtain a curve diagram showing the relationship between the differential value dpH / dV and the consumed volume VmL of the hydrochloric acid, wherein the dpH / dV is a differential value obtained by differentiating the pH value with respect to the consumed volume VmL of the hydrochloric acid;

[0007] In the relationship curve diagram of the differential value dpH / dV and the consumption volume VmL of the hydrochloric acid, the positive electrode material has a first characteristic peak when the consumption volume of the hydrochloric acid is V1mL, the positive electrode material has a last characteristic peak when the consumption volume of the hydrochloric acid is V2mL, and V1 and V2 satisfy the relationship: 0.6<V2-V1<2.7.

[0008] In some embodiments, 4<V1<8; and / or, 5<V2<11.

[0009] In some embodiments, in the relationship curve diagram of the differential value dpH / dV and the consumption volume V of the hydrochloric acid, the positive electrode material has N characteristic peaks in the interval range of the consumption volume V of the hydrochloric acid of 4 to 11 (excluding 4 and 11), and 2<N≤4.

[0010] In some embodiments, 0<dpH / dV<10.

[0011] The present application also provides a positive electrode material, the positive electrode material is a nickel cobalt lithium oxide composite oxide; the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material;

[0012] The positive electrode material was tested by XRD diffractometer, and the diffraction peak intensity of the (003) crystal plane of the positive electrode material was obtained to be I 003 , the diffraction peak intensity of (104) crystal plane is I 104 , and the grain size corresponding to the (104) crystal plane is calculated according to the Scherrer formula as D 104 ;

[0013] The positive electrode material satisfies: ε=log(D 104 ) / R, 0.90<ε<1.03, where R=I 003 / I 104 .

[0014] In some embodiments, 45 < D 104 <65.

[0015] In some embodiments, R>1.6.

[0016] In some embodiments, the chemical formula of the positive electrode material is LiNi a Co b Mn c M d Q e O2, wherein 0.8<a<0.98, b<0.2, c<0.2, a+b+c+d+e=1, M is the doping element, and Q is the coating element.

[0017] In some embodiments, the doping element M includes at least one of Sr, Ti, Al, Zr, Y, Ba, Mg, Nb, Mo, W, and V.

[0018] In some embodiments, the coating element Q includes at least one of S, W, F, P, and Mo.

[0019] In some embodiments, the conductivity of the positive electrode material is greater than 0.03 S / cm.

[0020] In some embodiments, the particle hardness G of the positive electrode material is D50 >80Mpa,G D90 >50Mpa.

[0021] In some embodiments, the particle hardness G of the positive electrode material is D50 >80Mpa,G D90 >50Mpa, and 1≤G D50 / G D90 ≤1.5.

[0022] In some embodiments, the average particle size D of the positive electrode material 50 9μm~12μm.

[0023] In some embodiments, the compaction density of the positive electrode material is greater than 3.0 g / cm 3 .

[0024] In some embodiments, the pH value of the positive electrode material is 11-12.

[0025] In some embodiments, the specific surface area of ​​the positive electrode material is greater than 0.2 m 2 / g.

[0026] In some embodiments, the positive electrode material has a tap density of >2.0 g / cm 3 .

[0027] In a second aspect, the present application provides a battery, comprising the positive electrode material described in the first aspect.

[0028] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects:

[0029] The positive electrode material provided in the present application is a nickel-cobalt lithium composite oxide; the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material; an acid-base potentiometric titration test is performed on the positive electrode material using a potentiometric titrator and hydrochloric acid with a concentration of 0.02 mol / L to obtain a curve diagram showing the relationship between the differential value dpH / dV and the consumption volume VmL of the hydrochloric acid, wherein the dpH / dV is a differential value obtained by differentiating the pH value with respect to the consumption volume VmL of the hydrochloric acid; in the curve diagram showing the relationship between the differential value dpH / dV and the consumption volume VmL of the hydrochloric acid, the positive electrode material has a first characteristic peak when the consumption volume of the hydrochloric acid is V1mL, and V1mL represents the consumption volume of the hydrochloric acid when the residual alkali on the surface of the positive electrode material begins to be neutralized, and the positive electrode material has a last characteristic peak when the consumption volume of the hydrochloric acid is V2mL, and V2mL represents the consumption volume of the hydrochloric acid when the residual alkali on the surface and inside of the positive electrode material is completely neutralized. During the entire acid-base neutralization process, in addition to the residual alkali on the surface of the material participating in the reaction, the elements in the coating layer formed after coating will also participate in the reaction. Therefore, the uniformity and thickness of the coating layer will affect the consumption of hydrochloric acid. The change in volume in the curve diagram of the relationship between the differential value dpH / dV and the consumption volume VmL of hydrochloric acid can indirectly reflect the state of the coating layer and the indirect reaction coating effect. In this application, the value of V2-V1 can reflect the coating effect of the coating layer on the surface of the positive electrode material to a certain extent. When the value of V2-V1 is between 0.6 and 2.7 (excluding 0.6 and 2.7), the coating layer on the surface of the positive electrode material is evenly distributed and has a good coating effect, which can reduce the surface residual alkali and impedance of the positive electrode material, so that the positive electrode material has both low gas production and low impedance, thereby improving the safety performance of the positive electrode material.

[0030] The positive electrode material provided in the present application is a nickel-cobalt-lithium composite oxide; the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material; the positive electrode material is tested by an XRD diffractometer, and the diffraction peak intensity of the (003) crystal plane of the positive electrode material is obtained to be I 003 , the diffraction peak intensity of (104) crystal plane is I 104 , and the grain size corresponding to the (104) crystal plane is calculated according to the Scherrer formula as D 104 ; Positive electrode material satisfies: ε=log(D 104 ) / R, 0.90<ε<1.03, where R=I 003 / I 104 In the present application, the grain size corresponding to the crystal plane of the positive electrode material (104) is D 104 The diffraction peak intensity I of the (003) and (104) crystal planes of the positive electrode material 003 / I 104There is a certain correlation, so ε can reflect the deviation of the grain growth and the ordered layered structure of the positive electrode material, such as the size, speed, and orientation consistency of the grain growth. When ε is close to 1, it indicates that the grain and layered structure of the positive electrode material have grown to the best, and the electrochemical performance of the positive electrode material is optimal. When ε deviates from 1 by a large amount, it indicates that the grain growth of the material is not ideal or the layered structure is not ideal, and the doping or coating fails to effectively modify the positive electrode material, reflecting that the electrochemical performance of the positive electrode material is poor. The ε value is an indicator for evaluating the deviation of the layered structure and crystal growth order of the positive electrode material from a microscopic perspective. When the value of the structural stability coefficient ε is between 0.90 and 1.03 (excluding 0.90 and 1.03), the grain size and ordered layered structure of the positive electrode material reach an ideal state. At this time, the positive electrode material has a suitable grain size and an ordered layered structure, which can improve the structural stability of the positive electrode material and improve the capacity and cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0032] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application;

[0033] Figure 2 A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Example 1 of the present application and the consumed volume V of hydrochloric acid;

[0034] Figure 3 A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Example 7 of the present application and the consumed volume V of hydrochloric acid;

[0035] Figure 4 A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Comparative Example 2 of the present application and the consumed volume V of hydrochloric acid;

[0036] Figure 5 A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Comparative Example 3 of the present application and the consumed volume V of hydrochloric acid;

[0037] Figure 6 XRD pattern of the positive electrode material prepared in Example 3 of the present application;

[0038] Figure 7 This is the particle size distribution diagram of the positive electrode material prepared in Example 7 of the present application.

[0039] Figure 1 middle:

[0040] 1-positive electrode sheet; 11-positive electrode current collector; 12-positive electrode active material layer; 2-negative electrode sheet; 21-negative electrode current collector; 22-negative electrode active material layer; 3-separator. DETAILED DESCRIPTION

[0041] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0042] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0044] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0045] In a first aspect, the present application provides a positive electrode material, the positive electrode material is a nickel cobalt lithium oxide composite oxide; the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material;

[0046] The positive electrode material is subjected to an acid-base potentiometric titration test using a potentiometric titrator and hydrochloric acid with a concentration of 0.02 mol / L to obtain a curve diagram showing the relationship between the differential value dpH / dV and the consumed volume VmL of the hydrochloric acid, wherein the dpH / dV is a differential value obtained by differentiating the pH value with respect to the consumed volume VmL of the hydrochloric acid;

[0047] In the relationship curve between the differential value dpH / dV and the consumption volume VmL of hydrochloric acid, the positive electrode material has the first characteristic peak when the consumption volume of hydrochloric acid is V1mL, and the positive electrode material has the last characteristic peak when the consumption volume of hydrochloric acid is V2mL, and V1 and V2 satisfy the relationship: 0.6<V2-V1<2.7.

[0048] In the above scheme, the positive electrode material is a nickel cobalt lithium composite oxide; the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material; an acid-base potentiometric titration test is performed on the positive electrode material using a potentiometric titrator and hydrochloric acid with a concentration of 0.02 mol / L to obtain a curve diagram showing the relationship between the differential value dpH / dV and the consumption volume VmL of the hydrochloric acid, wherein the dpH / dV is a differential value obtained by differentiating the pH value with respect to the consumption volume VmL of the hydrochloric acid; in the curve diagram showing the relationship between the differential value dpH / dV and the consumption volume VmL of the hydrochloric acid, the positive electrode material has a first characteristic peak when the consumption volume of the hydrochloric acid is V1mL, and V1 represents the consumption volume of the hydrochloric acid when the residual alkali on the surface of the positive electrode material begins to be neutralized, and the positive electrode material has a last characteristic peak when the consumption volume of the hydrochloric acid is V2mL, and V2mL represents the consumption volume of the hydrochloric acid when the residual alkali on the surface and inside of the positive electrode material is completely neutralized. During the entire acid-base neutralization process, in addition to the residual alkali on the surface of the material participating in the reaction, the elements in the coating layer formed after coating will also participate in the reaction. Therefore, the uniformity and thickness of the coating layer will affect the consumption of hydrochloric acid. The change in volume in the curve diagram of the relationship between the differential value dpH / dV and the consumption volume VmL of hydrochloric acid can indirectly reflect the state of the coating layer and the indirect reaction coating effect. In this application, the value of V2-V1 can reflect the coating effect of the coating layer on the surface of the positive electrode material to a certain extent. When V2-V1 is between 0.6 and 2.7 (excluding 0.6 and 2.7), the coating layer on the surface of the positive electrode material is evenly distributed and has a good coating effect, which can reduce the surface residual alkali and impedance of the positive electrode material, so that the positive electrode material has both low gas production and low impedance, thereby improving the safety performance of the positive electrode material.

[0049] It should be noted that the nickel cobalt oxide-based composite oxide, i.e., the nickel cobalt oxide-based positive electrode material in the present application may be a nickel cobalt manganese oxide (NCM) positive electrode material or a nickel cobalt aluminum oxide (NCA) positive electrode material.

[0050] In some embodiments, V1 and V2 satisfy the relationship: 0.6<V2-V1<2.7, which can be specifically 0.61, 0.65, 0.7, 1.0, 1.2, 1.5, 1.8, 2.0, 2.1, 2.3, 2.5 or 2.68, etc. Of course, it can also be other values ​​within the above range, which are not limited here. In the present application, V1mL represents the volume of hydrochloric acid consumed when the residual alkali on the surface of the positive electrode material begins to be neutralized, and V2mL represents the volume of hydrochloric acid consumed when the residual alkali on the surface and inside of the positive electrode material is completely neutralized. The value of V2-V1 can reflect the coating effect of the coating layer on the surface of the positive electrode material to a certain extent. When the value of V2-V1 is less than or equal to 0.6, the coating effect of the coating layer on the surface of the positive electrode material is not good, and the coating layer is difficult to completely coat the surface of the positive electrode material or is unevenly distributed on the surface of the positive electrode material, resulting in an increase in the residual alkali content on the surface of the positive electrode material, thereby increasing the gas production of the positive electrode material. When the value of V2-V1 is greater than or equal to 2.7, it indicates that a large volume of hydrochloric acid is consumed from the initial neutralization to the complete neutralization of the residual alkali in the positive electrode material during the titration process, which also indirectly indicates that there is excessive coating on the surface of the positive electrode material. At this time, due to the excessive coating material or coating product distributed on the surface of the positive electrode material, more hydrochloric acid is required to completely neutralize the residual alkali on the surface and inside of the positive electrode material; and excessive coating will cause the lithium ion transmission performance of the positive electrode material to decrease, and will also cause the capacity of the positive electrode material to decrease and the impedance to increase. Preferably, 1<V2-V1<2.7.

[0051] In some embodiments, 4<V1<8, specifically can be 4.1, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 7.6, 7.7, 7.8 or 7.9, etc., but is not limited to the listed values, other values ​​not listed in the numerical range are also applicable. When V1 is within this range, the surface byproducts of the positive electrode material (i.e., surface residual alkali, lithium hydroxide, lithium carbonate, etc.) are less, which is conducive to the preparation and coating of battery slurry.

[0052] In some embodiments, 5<V2<11, specifically can be 5.1, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or 10.9, etc., but is not limited to the listed values, other values ​​not listed in the numerical range are also applicable. When V2≥11, it means that the surface of the positive electrode material is excessively coated, resulting in an increase in the polarization rate of the positive electrode material, which is likely to accelerate the decrease in the energy density of the lithium-ion battery in the later stage.

[0053] In some embodiments, in the relationship curve between the differential value dpH / dV and the consumption volume VmL of hydrochloric acid, the positive electrode material has N characteristic peaks in the range of the consumption volume V of hydrochloric acid of 4 to 11 (excluding 4 and 11), and 2<N≤4. When N≥4, it indicates that the positive electrode material has more impurity ions (such as metal ions dissolved in the positive electrode material during the titration process, other inorganic impurity ions adsorbed on the surface of the positive electrode material, etc.) participating in the reaction, which is easy to interfere with the titration result, resulting in a larger V2-V1 value, thereby affecting the experimenter's judgment on the performance of the positive electrode material.

[0054] In some embodiments, 0<dpH / dV<10, specifically can be 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 9.5 or 9.9, etc., of course, it can also be other values ​​within the above range, which are not limited here. When the value of dpH / dV is within the above range, it means that the positive electrode material has a stable neutralization reaction during the titration process, and there are no extra impurity ions (such as hydroxide ions, carbonate ions, etc.) in the positive electrode material to interfere with the titration reaction, indicating that the elements in the positive electrode material are evenly distributed and the structural stability of the positive electrode material is good.

[0055] The present application also provides a positive electrode material, which is a nickel-cobalt-lithium oxide composite oxide; the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material;

[0056] The positive electrode material was tested by XRD diffractometer, and the diffraction peak intensity of the (003) crystal plane of the positive electrode material was obtained to be I 003 , the diffraction peak intensity of (104) crystal plane is I 104 , and the grain size corresponding to the (104) crystal plane is calculated according to the Scherrer formula as D 104 ; Positive electrode material satisfies: ε=log(D 104 ) / R, 0.90<ε<1.03, where R=I 003 / I 104 .

[0057] In the above scheme, the positive electrode material is a nickel cobalt lithium composite oxide; the positive electrode material includes a base material and a coating layer located on at least a portion of the surface of the base material; the positive electrode material is tested by an XRD diffractometer, and the diffraction peak intensity of the (003) crystal plane of the positive electrode material is obtained to be I 003 , the diffraction peak intensity of (104) crystal plane is I 104 , and the grain size corresponding to the (104) crystal plane is calculated according to the Scherrer formula as D 104 ; The structural stability coefficient of the positive electrode material satisfies: ε=log(D 104 ) / R, 0.90<ε<1.03, where R=I 003 / I 104In the present application, the grain size corresponding to the crystal plane of the positive electrode material (104) is D 104 The diffraction peak intensity I of the (003) and (104) crystal planes of the positive electrode material 003 / I 104 There is a certain correlation, so ε can reflect the deviation of the grain growth of the positive electrode material from the ordered layered structure. When the value of ε is between 0.90 and 1.03 (excluding 0.90 and 1.03), the grain size and ordered layered structure of the positive electrode material reach an ideal state. At this time, the positive electrode material has a suitable grain size and ordered layered structure, which can improve the structural stability of the positive electrode material, and improve the capacity and cycle performance of the positive electrode material.

[0058] In some embodiments, 0.90<ε<1.03, the value of ε can be 0.91, 0.92, 0.93, 0.94, 0.95, 0.98, 1.0, 1.01, 1.02 or 1.03, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. It can be understood that when the value of the structural stability coefficient ε is within the above range, the grain size and ordered layered structure of the positive electrode material reach an ideal state. At this time, the positive electrode material has a suitable grain size and an ordered layered structure, which can improve the structural stability of the positive electrode material and improve the capacity and cycle performance of the positive electrode material.

[0059] In some embodiments, 45 < D 104 <65, specifically can be 45.1, 45.5, 46, 48, 50, 55, 57, 60, 61, 62, 63, 64 or 64.8, etc., of course, it can also be other values ​​within the above range, which is not limited here. 104 When D is ≤45, the interatomic distance of the cathode material is relatively short, and the internal crystal structure of the cathode material is prone to form dislocations or stacking faults, which disrupts the orderliness of the layered structure of the cathode material, resulting in a decrease in the capacity of the cathode material. 104 When ≥65, the TM-O interlayer spacing (the interlayer spacing between the transition metal TM and oxygen O) of the positive electrode material will be enlarged, and lithium ions will easily cause structural collapse during repeated insertion and extraction, which will reduce the structural stability of the positive electrode material and thus lead to a decrease in the cycle performance of the positive electrode material.

[0060] In some embodiments, R = I 003 / I 104 , and R>1.6, specifically 1.61, 1.65, 1.68, 1.70, 1.72, 1.74, 1.77, 1.78 or 1.79, etc., but not limited to the listed values, other values ​​not listed in the numerical range are also applicable. When R≤1.6, I 003 The strength is weakened, I 104The strength is enhanced, and the disorder of the (104) crystal plane Ni layer and Li layer increases, resulting in the deterioration of the structural stability of the positive electrode material.

[0061] In some embodiments, the chemical formula of the positive electrode material is LiNi a Co b Mn c M d Q e O2, wherein 0.8<a<0.98, b<0.2, c<0.2, a+b+c+d+e=1, M is a doping element, and Q is a coating element. The value of a can be 0.81, 0.83, 0.86, 0.89, 0.9, 0.91, 0.93, 0.95, 0.96 or 0.97, etc., the value of b can be 0.001, 0.01, 0.05, 0.1, 0.15, 0.16, 0.17 or 0.19, etc., and the value of c can be 0.001, 0.01, 0.05, 0.1, 0.15, 0.16, 0.18 or 0.19, etc., which are not limited here.

[0062] In some embodiments, the doping element M includes at least one of Sr, Ti, Al, Zr, Y, Ba, Mg, Nb, Mo, W, and V.

[0063] In some embodiments, the coating element Q includes at least one of S, W, F, P, and Mo.

[0064] In some embodiments, the conductivity of the positive electrode material is greater than 0.03S / cm, and specifically may be 0.035S / cm, 0.038S / cm, 0.04S / cm, 0.05S / cm, 0.06S / cm, 0.07S / cm, 0.08S / cm, 0.1S / cm or 0.2S / cm, etc., and of course may also be other values ​​within the above range, which are not limited here. The conductivity of the positive electrode material within the above range is conducive to improving the lithium ion transmission efficiency and improving the rate performance of the positive electrode material.

[0065] In some embodiments, the particle hardness G of the positive electrode material is D50 >80Mpa,G D90 >50Mpa,G D50 Specifically, it can be 80.1Mpa, 85.8Mpa, 90.9Mpa, 94.4Mpa, 99.8Mpa, 103.5Mpa, 105.7Mpa, 109.9Mpa, 119.4Mpa, 131Mpa, 155.3Mpa or 200Mpa, etc. D90Specifically, it can be 50.1Mpa, 60.2Mpa, 65.5Mpa, 77.7Mpa, 82.8Mpa, 85.9Mpa, 88.8Mpa, 90.2Mpa, 93.5Mpa, 94.9Mpa, 105.3Mpa, 120.1Mpa, 130.6Mpa, 141.1Mpa or 160Mpa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0066] According to in-depth research, the ε value can also affect the mechanical properties of the positive electrode material and the particle hardness G of the positive electrode material from a macroscopic perspective. D50 and particle hardness G D90 The applicant analyzed and speculated that the enhanced bonding force between the positive electrode material matrix and the coating material is conducive to improving the particle hardness of the material, among which the particle hardness G D50 Represents the high hardness of most particles. When the particle hardness G of the positive electrode material is D50 When it is >80Mpa, it can resist the external extrusion pressure, disperse the internal extrusion pressure and disperse the internal stress. Moreover, when the ε range is adjusted to 0.90~1.03 (excluding 0.90 and 1.03), G D90 This indicates that large particles in the positive electrode material can also have high hardness, thus improving the overall uniformity and hardness of the positive electrode material particles. D50 , G D90 The coordination between them not only regulates the structural stability of the cathode material from the macroscopic overall particle system, but also achieves the structural stability of the cathode material from the individual particle. In addition, the interaction of the above parameters also shows that the concave and convex gaps between the primary particles of the cathode material are further adjusted and compensated, and the mechanical stability of the material is also improved.

[0067] In some embodiments, the particle hardness of the positive electrode material satisfies the relationship: 80Mpa<G D50 <110Mpa,50Mpa<G D90 <95Mpa,G D50 Specifically, it can be 80.1Mpa, 85.8Mpa, 90.9Mpa, 94.4Mpa, 99.8Mpa, 103.5Mpa, 105.7Mpa or 109.9Mpa, etc. D90 Specifically, it can be 50.1Mpa, 60.2Mpa, 65.5Mpa, 77.7Mpa, 82.8Mpa, 85.9Mpa, 88.8Mpa, 90.2Mpa, 93.5Mpa or 94.9Mpa, etc. Of course, it can also be other values ​​within the above range, which is not limited here. Theoretically, the hardness G of the positive electrode material D50 and G D90The bigger the better, but too high particle hardness may affect the processing performance of the positive electrode material. D50 and G D90 When the content is controlled within the above range, the electrical properties of the positive electrode material particles can be further optimized.

[0068] In some embodiments, 1.0≤G D50 / G D90 ≤1.5, specifically 1.10, 1.16, 1.19, 1.22, 1.25, 1.28, 1.31, 1.36, 1.40, 1.44, 1.47 or 1.50, etc., but not limited to the listed values, other values ​​not listed in the range are also applicable. D50 / G D90 When the positive electrode material particles are within the above range, not only the overall coating is uniform and the structure is stable, but also the D 90 The hardness of large particles at the level of D 50 The difference in hardness between the large particles at the same level maintains the overall system energy of the positive electrode material at a low level, further improving the mechanical properties while also being more conducive to uniform dispersion of the particles.

[0069] In some embodiments, the average particle size D of the positive electrode material is 50 The average particle size of the positive electrode material is 9 μm to 12 μm, and specifically can be 9 μm, 9.2 μm, 9.5 μm, 9.8 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm, 11.8 μm or 12 μm, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. The average particle size of the positive electrode material is within the above range, which is conducive to improving the structural stability, thermal stability and long cycle stability of the positive electrode material.

[0070] In some embodiments, the compaction density of the positive electrode material is greater than 3.0 g / cm 3 , specifically 3.1 g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 or 3.7 g / cm 3 Of course, it can also be other values ​​within the above range, which is not limited here. The compaction density of the positive electrode material is within the above range, which is conducive to improving the energy density of the battery made of the positive electrode material.

[0071] In some embodiments, the pH value of the positive electrode material is 11-12, specifically 11, 11.1, 11.2, 11.3, 11.4, 11.5, 11.6, 11.7, 11.8, 11.9 or 12, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0072] In some embodiments, the specific surface area of ​​the positive electrode material is greater than 0.2 m 2 / g, specifically 0.25m 2 / g, 0.28m 2 / g, 0.3m 2 / g, 0.35m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1m 2 / g, 1.2m 2 / g or 1.5m 2 / g, etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. The specific surface area of ​​the positive electrode material is controlled within the above range, and there is a good contact area between the positive electrode material and the electrolyte, which is conducive to the transmission and diffusion of lithium ions and is conducive to improving the cycle performance and rate performance of the lithium battery made of the positive electrode material.

[0073] In some embodiments, the positive electrode material tap density is > 2.0 g / cm 3 , specifically 2.1 g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 , 3g / cm 3 、3.1g / cm 3 , 3.3g / cm 3 or 3.5g / cm 3 The above range is not limited to the listed values, and other values ​​not listed within the above range are also applicable.

[0074] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:

[0075] Step S100, mixing a hydroxide precursor, a lithium source and a dopant containing an M element uniformly to form a mixture;

[0076] Step S200, performing a first sintering treatment on the mixture at 600° C. to 800° C. in an oxygen-containing atmosphere to obtain a base material;

[0077] Step S300, spraying and dropping a coating solution containing Q element into the above-mentioned base material for coating treatment;

[0078] Step S400, in an oxygen-containing atmosphere, subjecting the coated product to a second sintering treatment to obtain a positive electrode material.

[0079] In the above scheme, a mixture containing a hydroxide precursor, a lithium source and a dopant containing an M element is first sintered in an oxygen-containing atmosphere to obtain a matrix material. By controlling the temperature of the first sintering process, the grain size D of the positive electrode material can be controlled. 104 , thereby reducing the formation of dislocations or stacking faults in the crystal structure of the positive electrode material, improving the orderliness of the layered structure of the positive electrode material, improving the structural stability of the positive electrode material, and further improving the capacity and cycle performance of the positive electrode material. Secondly, the coating solution containing the Q element is sprayed and dripped into the above-mentioned base material for coating treatment. The coating uniformity can be improved by spraying and dripping, so that the coating solution containing the Q element is uniformly and completely coated on the surface of the base material; finally, the product after the coating treatment is subjected to a second sintering treatment. During the second sintering treatment, the coating solution containing the Q element forms a uniform and complete coating layer on the surface of the base material. At the same time, the residual lithium on the surface of the base material can react with the coating material to form a lithium composite metal oxide attached to the surface of the base material to form a coating layer, which can reduce the surface residual alkali and impedance of the positive electrode material, so that the positive electrode material has both low gas production and low impedance, thereby improving the safety performance of the positive electrode material. The following is a detailed introduction to the preparation method of the present application in combination with the above-mentioned embodiments:

[0080] In step S100 , a hydroxide precursor, a lithium source and a dopant containing an M element are uniformly mixed to form a mixture.

[0081] In some embodiments, the hydroxide precursor has the formula Ni a Co b Mn c (OH)2, wherein 0.8<a<0.98, 0<b<0.2, 0<c<0.2, a+b+c=1. The value of a can be 0.81, 0.83, 0.86, 0.89, 0.9, 0.91, 0.93, 0.95, 0.96 or 0.97, etc., the value of b can be 0.001, 0.01, 0.05, 0.1, 0.15, 0.16, 0.17 or 0.19, etc., and the value of c can be 0.001, 0.01, 0.05, 0.1, 0.15, 0.16, 0.18 or 0.19, etc., which are not limited here.

[0082] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate. Preferably, the lithium source is lithium hydroxide, specifically lithium hydroxide monohydrate or anhydrous lithium hydroxide, which is not limited here.

[0083] In some embodiments, the molar ratio of Li in the lithium source to the metal element in the hydroxide precursor is 0.9-1.1, specifically 0.9, 0.92, 0.95, 0.98, 1.0, 1.01, 1.02, 1.03, 1.05, 1.08 or 1.1, etc., and of course other values ​​within the above range are also possible, which are not limited here.

[0084] In some embodiments, the mass ratio of the dopant containing the M element to the hydroxide precursor is less than 0.1, and can be specifically 0.098, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02 or 0.01, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0085] In some embodiments, the dopant containing the M element includes at least one of Sr(OH)2, SrO, TiO2, Al2O3, Al(OH)3, ZrO2, Zr(OH)4, Y2O3, BaO, MgO, Mg(OH)2, Nb2O5, Nb2O3, MoO3, WO2, WO3, V2O5, V2O3. Preferably, Al(OH)3, Sr(OH)2, WO3.

[0086] In some embodiments, the mixing time is 0.5 h to 1 h, specifically 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h or 1 h, etc., and of course other values ​​within the above range are also possible, which are not limited here. Preferably, the mixing time is 0.5 h.

[0087] Step S200 , performing a first sintering treatment on the mixture at 600° C. to 800° C. in an oxygen-containing atmosphere to obtain a base material.

[0088] In some embodiments, the temperature of the first sintering treatment is 600°C to 800°C, specifically 600°C, 620°C, 650°C, 700°C, 750°C, 780°C or 800°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0089] In some embodiments, the time of the first sintering treatment is 8 h to 25 h, specifically 8 h, 10 h, 12 h, 15 h, 18 h, 20 h, 22 h, 24 h or 25 h, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0090] It can be understood that the present invention is beneficial to control the grain size D of the positive electrode material by controlling the temperature and time of the first sintering process within the above range. 104, thereby reducing the formation of dislocations or stacking faults in the crystal structure of the positive electrode material, improving the orderliness of the layered structure of the positive electrode material, improving the structural stability of the positive electrode material, and thus improving the capacity and cycle performance of the positive electrode material.

[0091] In some embodiments, the oxygen inlet rate is controlled to be 40 m3 / h at the bottom, 20 m3 / h at the left and right sides, and 30 m3 / h at the top. The pressure in the calcining chamber is controlled to be 30 Pa.

[0092] In some embodiments, the method further includes crushing and screening the sintered product to obtain a matrix material.

[0093] In some embodiments, the screening uses an ultrasonic vibration screener, and the frequency of the ultrasonic vibration screener used is 20KHz to 50KHz, specifically 20KHz, 25KHz, 30KHz, 35KHz, 40KHz, 45KHz or 50KHz, etc., which are not limited here. It can be understood that screening the sintered product using an ultrasonic vibration screener can ensure that the base material particles are evenly dispersed, reduce the agglomeration of the base material particles, and improve the coating uniformity of the base material and the coating material.

[0094] In some embodiments, the average particle size of the matrix material is 9 μm to 12 μm, specifically 9 μm, 9.2 μm, 9.5 μm, 10 μm, 11 μm, 11.5 μm, 11.8 μm or 12 μm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Preferably, the average particle size of the matrix material is 10.5 μm.

[0095] Step S300, spraying and dropping a coating solution containing Q element into the above-mentioned base material for coating treatment.

[0096] In some embodiments, before step S300, the method further includes: dissolving a coating agent containing the Q element in water to form a coating solution containing the Q element.

[0097] In some embodiments, based on the mass of the positive electrode material as 100%, the amount of water added to the coating solution is 1% to 10%, specifically 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and of course, it can also be other values ​​within the above range, which are not limited here.

[0098] In some embodiments, the mass ratio of the Q-containing coating agent to the base material is less than 0.1, and can be 0.098, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02 or 0.01, etc., and can also be other values ​​within the above range, which are not limited here. Preferably, the mass ratio of the Q-containing coating agent to the base material is 0.01 to 0.04.

[0099] In some embodiments, the coating treatment is carried out under stirring, and the stirring temperature is 100°C to 300°C, specifically 100°C, 120°C, 150°C, 180°C, 200°C, 240°C, 280°C or 300°C, etc., which is not limited here; the stirring time is 0.5h to 2h, specifically 0.5h, 0.8h, 1.0h, 1.1h, 1.2h, 1.5h, 1.8h or 2h, etc., which is not limited here.

[0100] The present application can improve the coating uniformity of the coating agent on the base material by controlling the stirring time and temperature during the coating process within the above range.

[0101] In some embodiments, the Q-containing coating agent includes (NH4)2SO4, NH4HSO4, (NH4)6W7O 24 6H2O、H 28 N6O 41 W 12 , H 18 N3O 43 PW 12 , NH4F, NH4HF, (NH4)3PO4, (NH4)2HPO4, (NH4)2MoO4, at least one of.

[0102] In some embodiments, the spray frequency is controlled in the form of "spot spraying", that is, a pulse current is set, the solution will continue to spray for 5 seconds, stop for 10 seconds, and so on until the solution spraying is finished, and the spray flow rate is set to 1ml / min. The spray pressure is controlled by a frequency converter, that is, the pressure at the beginning of the spraying is 10kpa, and the pressure at the end of the pulse spraying is 20kpa.

[0103] It can be understood that the present application reserves a certain reaction time for the positive electrode material and the coating material by controlling the pulse "spot spraying" method during the coating process, and continues to spray after the reaction is completed. At the same time, the spray range is related to the spray pressure. In a cycle of "spot spraying", comprehensive coating from a small range to a large range can be achieved. Under such a cyclic spray injection, sufficient reaction area is reserved for the positive electrode material and the coating agent. During the continuous flipping of the material, the intermittent addition of the solution can improve the uniformity of the interface reaction, while further stabilizing the material interface structure and filling the micro gaps between the primary particles. Therefore, the mechanical properties of the positive electrode material, such as particle strength, are enhanced.

[0104] Step S400, in an oxygen-containing atmosphere, subjecting the coated product to a second sintering treatment to obtain a positive electrode material.

[0105] In some embodiments, the temperature of the second sintering treatment is 200°C to 600°C, specifically 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or 600°C, etc., and of course other values ​​within the above range are also possible, which are not limited here. Preferably, the temperature of the second sintering treatment is 300°C.

[0106] In some embodiments, the second sintering treatment time is 6 hours to 12 hours, specifically 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Preferably, the second sintering treatment time is 8 hours.

[0107] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.

[0108] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.

[0109] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.

[0110] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0111] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .

[0112] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.

[0113] In some embodiments, the preparation method of the positive electrode sheet 1 is: the positive electrode active material, the conductive agent, the binder and the solvent are mixed uniformly in a certain proportion to form a slurry, and then the slurry is uniformly coated on the positive electrode collector 11, and vacuum dried at a certain temperature to obtain the positive electrode sheet 1.

[0114] In some embodiments, the conductive agent includes at least one of conductive carbon black, Ketjen black, graphite, and acetylene black.

[0115] In some embodiments, the binder includes at least one of sodium carboxymethyl cellulose, cyclodextrin, and polyvinylidene fluoride.

[0116] In some embodiments, the solvent is selected from at least one of deionized water, N-methylpyrrolidone, and N,N-dimethylformamide.

[0117] In some embodiments, the vacuum drying temperature is 60°C to 120°C, specifically 60°C, 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0118] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.

[0119] In some embodiments, the negative electrode current collector 21 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to at least one of natural graphite negative electrode material, natural graphite negative electrode material or silicon-based negative electrode material.

[0120] Example 1

[0121] (1) LiOH·H2O, hydroxide precursor Ni 0.9 Co 0.09 Mn 0.01 (OH)2 is uniformly mixed with Al(OH)3, 0.4wt% Sr(OH)2 and 0.2wt% WO3 in a molar ratio of 1.02 and a doping amount of 0.3wt% of the mass of the precursor to obtain a mixture;

[0122] (2) sintering the mixture at 720° C. for 12 h in an oxygen-containing atmosphere, cooling, crushing, and screening the primary sintered product to obtain a matrix material;

[0123] (3) 0.2 g of ammonium tungstate (NH4)6W7O 24 ·6H2O was dissolved in 5g of deionized water to form a coating solution; 50g of the above-mentioned matrix material was added into a reactor, and the temperature of the reactor was raised to 200°C. The coating solution was transferred to a spray system and added dropwise into the reactor. After all the coating solution was dripped into the reactor, it was stirred for 2h to obtain a coated product.

[0124] (4) The coated product was sintered at 450° C. for 5 h in an oxygen-containing atmosphere, cooled, and sieved to obtain a positive electrode material.

[0125] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8948 Co 0.0895 Mn 0.0099 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0126] Figure 2 A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Example 1 of the present application and the consumed volume VmL of hydrochloric acid; Figure 2 It can be seen that the positive electrode material has four characteristic peaks in the range of hydrochloric acid consumption volume V of 4 to 11 (excluding 4 and 11), and the value of V2-V1 is 2.6.

[0127] Example 2

[0128] The difference from Example 1 is that the doping amount of the dopant Al(OH)3 in step (1) is 0.6 wt% of the mass of the precursor.

[0129] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8940 Co 0.0894 Mn 0.0099 Al 0.0021 Sr 0.001 3W 0.0033 O2.

[0130] Example 3

[0131] The difference from Example 1 is that the doping amount of the dopant Sr(OH)2 in step (1) is 0.8 wt% of the mass of the precursor.

[0132] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8936 Co 0.0894 Mn 0.0099 Al 0.0012 Sr 0.002 6W 0.0033 O2.

[0133] Example 4

[0134] The difference from Example 1 is that the doping amount of WO3 in step (1) is changed to 0.3 wt% of the mass percentage of the precursor.

[0135] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8941 Co 0.0894 Mn 0.0099 Al 0.0010 Sr 0.001 3W 0.0043 O2.

[0136] Example 5

[0137] The difference from Example 1 is that the sintering temperature in step (2) is 690°C.

[0138] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8948 Co 0.0895 Mn 0.0099 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0139] Example 6

[0140] The difference from Example 1 is that the sintering temperature in step (2) is 750°C.

[0141] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8948 Co 0.0895 Mn 0.0099 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0142] Example 7

[0143] The difference from Example 1 is that in step (3), the temperature of the reactor is adjusted to 50°C.

[0144] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8948 Co 0.0895 Mn 0.0099 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0145] Figure 3 A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Example 7 of the present application and the consumed volume VmL of hydrochloric acid; Figure 3 It can be seen that the positive electrode material has four characteristic peaks in the range of hydrochloric acid consumption volume V of 4 to 11 (excluding 4 and 11), and the value of V2-V1 is 1.82.

[0146] Example 8

[0147] The difference from Example 1 is that the hydroxide precursor in step (1) is Ni 0.85 Co 0.1 0Mn 0.05 (OH)2, in step (3), the temperature of the reactor is adjusted to 250°C.

[0148] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8451 Co 0.0994 Mn 0.0497 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0149] Example 9

[0150] The difference from Example 1 is that the hydroxide precursor in step (1) is Ni 0.95 Co 0.025 Mn 0.025 (OH)2, the sintering temperature in step (4) is 200°C.

[0151] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.9445Co 0.02485 Mn 0.02485 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0152] Example 10

[0153] The difference from Example 1 is that the hydroxide precursor in step (1) is Ni 0.88 Co 0.09 Mn 0.03 (OH)2, the sintering temperature in step (4) is 300°C.

[0154] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8749 Co 0.0894 Mn 0.0299 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0155] Embodiment 11

[0156] The difference from Example 1 is that the first sintering temperature in step (2) is 600°C.

[0157] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8948 Co 0.0895 Mn 0.0099 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0158] Example 12

[0159] The difference from Example 1 is that the amount of deionized water used in step (3) is reduced to 2 g.

[0160] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8948 Co 0.0895 Mn 0.0099 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0161] Embodiment 13

[0162] The difference from Example 1 is that in step (3), the spraying time is 10 seconds and the dwell time is 15 seconds.

[0163] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8948 Co 0.0895 Mn 0.0099 Al0.0012 Sr 0.001 3W 0.0033 O2.

[0164] Embodiment 14

[0165] The difference from Example 1 is that the injection flow rate in step (3) is 0.5 ml / min.

[0166] Embodiment 15

[0167] The difference from Example 1 is that the injection flow rate in step (3) is 1.5 ml / min.

[0168] Example 16

[0169] The difference from Example 1 is that in step (3), the pulse start injection pressure is 20 KPa, and the pulse end injection pressure is 30 KPa.

[0170] Embodiment 17

[0171] The difference from Example 1 is that in step (1), the precursor is Ni 0.805 CO 0.105 Mn 0.09 (OH)2.

[0172] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.8004 Co 0.1044 Mn 0.0894 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0173] Embodiment 18

[0174] The difference from Example 1 is that in step (1), the precursor is Ni 0.98 CO 0.01 Mn 0.01 (OH)2.

[0175] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.9744 Co 0.0099 Mn 0.0099 Al 0.0012 Sr 0.001 3W 0.0033 O2.

[0176] Comparative Example 1

[0177] The difference from Example 1 is:

[0178] (2) sintering the mixture at 820° C. for 20 h in an oxygen-containing atmosphere, cooling, crushing, and screening the primary sintered product to obtain a matrix material;

[0179] (3) 0.2 g of ammonium tungstate (NH4)6W7O 24 ·6H2O was dissolved in 5g of deionized water to form a coating solution; 50g of the above-mentioned matrix material was added into the reactor, and the temperature of the reactor was raised to 200°C, and then the coating solution was continuously sprayed into the reactor at a speed of 1ml / min by direct current spraying. After all the coating solution was dripped into the reactor, it was stirred for 2h to obtain a coated product.

[0180] Comparative Example 2

[0181] The difference from Example 1 is:

[0182] (3) 50 g of the above matrix material was added into a reactor, and the reactor temperature was raised to 200°C, and then 0.2 g of ammonium tungstate (NH4)6W7O was added thereto. 24 ·6H2O, stirred for 2h to obtain the coated product.

[0183] Figure 4 A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Comparative Example 2 of the present application and the consumed volume VmL of hydrochloric acid; Figure 4 As shown, the positive electrode material after dry coating has only two sudden peaks in the potentiometric titration, which means that the dry coating method may not successfully coat the coating agent on the surface of the base material, or the coating agent is less distributed on the surface of the base material. During the titration process, the titrant hydrochloric acid fails to react with the coating material or the coating product, so that no sudden peak can be detected.

[0184] Comparative Example 3

[0185] The difference from Example 1 is:

[0186] (2) sintering the mixture at 580° C. for 12 h in an oxygen-containing atmosphere, cooling, crushing, and screening the primary sintered product to obtain a matrix material;

[0187] (3) 0.2 g of ammonium tungstate (NH4)6W7O 24 ·6H2O was dissolved in 100g of deionized water to form a coating solution; 50g of the above-mentioned matrix material was added into a reactor, and the temperature of the reactor was raised to 200°C, and then the coating solution was dripped into the reactor using a rubber-tipped dropper. After all the coating solution was dripped into the reactor, it was stirred for 2h to obtain a coated product.

[0188] Figure 5A curve diagram showing the relationship between the differential value dpH / dV of the positive electrode material provided in Comparative Example 3 of the present application and the consumed volume VmL of hydrochloric acid; Figure 5 As shown, the potentiometric titration peak has more impurities. This is because during the wet coating process, water washing causes more lithium ions to be dissolved from the surface of the positive electrode material, resulting in more ions (such as metal ions dissolved during the hydrolysis process, etc.) interfering with the titration results.

[0189] Test Method

[0190] (1) Potentiometric titration test:

[0191] Take 5g of positive electrode material and disperse it in 100ml of deionized water. Dissolve the residual carbonate and hydroxide by magnetic stirring. After filtration, the filtrate is obtained, and hydrochloric acid is added to the automatic potentiometric titrator for titration in an equivalent dropwise manner. The reading mode adopts the "PH" method, and the "dPH / dV" differential fitting is performed through the pH value change and the consumption of hydrochloric acid solution to obtain the fitted differential curve. The distance between the first peak and the last peak is calculated through the sudden peak of the curve to judge the gas production and other properties of the positive electrode material. In addition, the content of carbonate and hydroxide in the positive electrode material can also be calculated based on the situation of the sudden point and the amount of hydrochloric acid consumed.

[0192] (2) XRD test:

[0193] The sample (positive electrode material) was characterized by XRD using an XRD diffractometer (RIGAICU UITIMAIV) with a scanning range of 10-90° and a scanning step of 0.05°. The incident angle (2θ), interplanar spacing (d), full width at half maximum (FWHM) and other parameters of the sample (positive electrode material) were read using the Jade software, and then the Scherrer formula was used to calculate D 104 The value of .

[0194] (3) Conductivity test of positive electrode materials:

[0195] Use a resistivity tester (Suzhou Jingge Electronics ST-2255A), take 5g of powder sample, use an electronic press to press it to 5000kg±2kg, and maintain it for 15-25s. Place the sample between the electrodes of the tester, the sample height is h (cm), the voltage at both ends is U, the current is I, and the area after the powder is pressed is S = 3.14cm 2 The electronic conductivity of the powder is calculated according to the formula σ=h / (S×R) / 1000.

[0196] (4) Compaction density test of positive electrode materials:

[0197] The metal content of the positive electrode material was tested using the American Agilent 5110 ICP-OES. 0.2 g of the positive electrode material was dissolved in a mixture of nitric acid and hydrochloric acid (volume ratio 3:1), heated and digested, and the volume was fixed to 100 ml, and then the instrument was used to read the data.

[0198] (5) pH value test of positive electrode material:

[0199] The pH value of the material was measured using a Mettler pH meter. 5 g of powder sample was dissolved in 45 ml of pure water, stirred at a certain speed for 30 min, and then tested with a pH meter. The pH values ​​of the standard solutions were 4.01 / 7.0 / 9.21, respectively.

[0200] (6) Specific surface area test of positive electrode materials:

[0201] The specific surface area of ​​the positive electrode material is measured by the gas adsorption method. Specifically, Micromeritics Tristar II is used to perform N2 adsorption test and calculate the adsorption amount under different equilibrium pressures, and the isothermal adsorption line is obtained to calculate the specific surface area of ​​the positive electrode material.

[0202] (7) Tap density test of positive electrode materials:

[0203] Using a vibrator, weigh a certain amount of sample and vibrate 3000 times at 300 times / min to test the tap density.

[0204] (8) Testing method for particle size of positive electrode materials:

[0205] The particle size distribution range of the positive electrode material was tested by Malvern laser particle size analyzer.

[0206] (9) Particle hardness G of positive electrode material D50 and G D90 test:

[0207] Using Shimadzu dynamic ultramicrohardness tester, randomly select three or more complete positive electrode material particles with a particle size in the range of 9um-13um and three or more complete positive electrode material particles with a particle size in the range of 16um-20um under the display of the instrument, use the probe to apply a certain pressure to the positive electrode material particles, record the deformation displacement of the particles, and record the pressure applied when the particles are broken, and calculate the average value respectively. The particle hardness of the positive electrode material is calculated and recorded as G D50 and G D90 .

[0208] (10) Electrochemical performance test:

[0209] Take 0.8g positive electrode material, 0.1g conductive carbon black, and 0.1g polyvinylidene fluoride and put them into a ball mill, add 15mL N-methylpyrrolidone, ball mill to form a uniform slurry, then evenly coat it on aluminum foil, and vacuum dry it at 110℃ for 12h to obtain a positive electrode. Cut the dried electrode into a disc with a diameter of 15mm, assemble and seal the positive electrode shell, electrode, electrolyte (EC / DMC / EMC volume ratio 1:1:1, LiPF6 concentration is 1mol / L), diaphragm (Celgard PP / PE / PP three-layer composite film), lithium sheet, electrolyte, nickel foam, and negative electrode shell in a glove box to obtain a button battery and let it stand for 24h. Then put the obtained battery into a constant temperature box for testing.

[0210] DC resistance test:

[0211] The battery was discharged to 2.0V at a current density of 1C, and then charged to 4.2V at a current density of 1C after standing for 2 minutes. The above steps were repeated for 50 cycles. The battery was fully charged to 4.2V and kept for 1 hour. Then the battery was adjusted to 100% SOC at a current density of 1C and stood for 30 minutes. The voltage V0 at this time was recorded. The discharge current ts of 1C was used, and the voltage V1 at ts was recorded. The DC resistance at the 50th week was calculated based on (V0-V1) / It.

[0212] Power-off performance test:

[0213] The LAND battery testing system was used to conduct discharge capacity (0.1C / 0.5C / 1C) and first-cycle charge and discharge efficiency performance tests at 25°C and 3.0V to 4.3V. The reference capacity was set to 200mA / g, and 1C corresponded to a current density of 200mA / g.

[0214] (10) Soft pack battery volume expansion rate test:

[0215] The positive electrode materials and graphite negative electrodes prepared in Examples 1 to 18 and Comparative Examples 1 to 3 were respectively made into pole pieces, and soft-pack batteries were prepared by lamination, pole ear welding, shell punching, packaging, liquid injection, pre-charging, formation, degassing, etc. The prepared soft-pack battery was immersed in a beaker filled with deionized water, and the scale V0 at this time was recorded. Then, the soft-pack battery after 60°C high temperature cycle for 50 weeks, 100 weeks, and 200 weeks was immersed in the beaker in turn, and the scale V3 at this time was recorded. The volume expansion rate of the soft-pack battery was calculated according to (V3-V0) / V0*100.

[0216] The above test results are detailed in Tables 1 to 3.

[0217] Table 1 Physical and chemical properties test results of positive electrode materials

[0218]

[0219] Table 2 Electrochemical performance test results of positive electrode materials

[0220]

[0221]

[0222] According to the test data in Table 2, the positive electrode materials prepared in Examples 1 to 18 are obtained by controlling the grain size D corresponding to the (104) crystal plane. 104 , (003) crystal plane and (104) crystal plane diffraction peak intensity I 003 / I 104 The relationship between ε and the order of the layered structure can be balanced, and the grain size and the ordered layered structure of the positive electrode material can reach an ideal state, so that the positive electrode material has a suitable grain size and an ordered layered structure, which can improve the structural stability of the positive electrode material, and improve the capacity and cycle performance of the positive electrode material.

[0223] According to the test data of Example 1 and Example 2, the amount of Al(OH)3 was increased in Example 2, and the capacity of the positive electrode material decreased. It can be seen that excessive doping of inert elements will occupy the TM-O-Li layer, resulting in a decrease in the capacity and cycle performance of the positive electrode material.

[0224] According to the test data of Example 1 and Example 5, the positive electrode material of Example 5 has a grain size D 104 The atomic distance between small-sized particles is relatively short, which is easy to form dislocation or stacking fault. The order of the layered structure of the positive electrode material is disrupted, and lithium-nickel mixing is likely to occur, resulting in the diffraction peak intensity I of the (003) crystal plane and the (104) crystal plane of the positive electrode material. 003 / I 104 The ratio is reduced, resulting in a higher ε value, and the capacity and cycle performance of the positive electrode material are reduced compared to Example 1.

[0225] According to the test data of Example 1 and Example 11, the positive electrode material of Example 11 has a grain size D 104 The atomic distance between the positive electrode material particles is smaller, the crystal structure of the positive electrode material is prone to dislocation or stacking fault, and the orderliness of the layered structure of the material is reduced, resulting in a decrease in the capacity and cycle performance of the positive electrode material compared to Example 1.

[0226] According to the test data of Example 1 and Comparative Example 1, the temperature of the primary sintering of the positive electrode material in Comparative Example 1 is too high during the preparation process, resulting in a grain size D 104 If the value of ε is too large, the positive electrode material's ε value will be too large, and the positive electrode material's grain size and ordered layered structure will be difficult to reach an ideal state. The positive electrode material's structural stability will decrease, which will lead to a decrease in the positive electrode material's capacity and cycle performance.

[0227] According to the test data of Example 1 and Comparative Example 2, the positive electrode material of Comparative Example 2 is dry coated during the preparation process. During the coating process, the coating material on the surface of the base material is unevenly distributed. Therefore, during the second sintering process, the coating material will form uneven penetration on the surface of the positive electrode material, thereby destroying the layered structure on the surface of the positive electrode material and reducing the grain size D of the positive electrode material. 104 Compared with Example 1, the diffraction peak intensity I of the (003) crystal plane and the (104) crystal plane is increased. 003 / I 104 The ratio decreases, resulting in an excessively large ε value of the prepared positive electrode material, making it difficult for the grain size and ordered layered structure of the positive electrode material to reach an ideal state, and the capacity and cycle performance of the positive electrode material decrease.

[0228] According to the test data of Example 1 and Comparative Example 3, the amount of deionized water added to the positive electrode material of Comparative Example 3 during the preparation of the coating solution is too much. During the coating process, the base material particles are very sensitive to water. When the particle surface is oxidized, the surface layered structure of the positive electrode material is easily transformed into a spinel structure or a rock salt phase, and the Ni-O oxide of the 003 crystal face or the 104 crystal face with more exposed surfaces is easily converted into impurities such as NiO or NiOOH, resulting in I 003 / I 104 The ratio increases; at the same time, due to the low first sintering temperature, the grain size D of the positive electrode material 104 The ε value of the prepared positive electrode material is too small, and the grain size and ordered layered structure of the positive electrode material are difficult to reach an ideal state, and the capacity and cycle performance of the positive electrode material are reduced.

[0229] Table 3 Battery performance test results of positive electrode materials

[0230]

[0231]

[0232] According to the test data in Table 3, the positive electrode materials prepared in Examples 1 to 18 have a V2-V1 value between 0.6 and 2.7 (excluding 0.6 and 2.7), and the coating material on the surface of the positive electrode material is evenly distributed and has a good coating effect, which can reduce the surface residual alkali and impedance of the positive electrode material, so that the positive electrode material has both low gas production and low impedance, thereby improving the safety performance of the positive electrode material.

[0233] Compared with Example 1, Example 7 adopts a low-temperature coating method during the coating reaction. However, according to the volume expansion results of the soft-pack battery in Table 3, it can be seen that the gas production of Example 7 has not been improved. When the battery is cycled for 200 weeks, its volume expands to 25.1%. This is because the decomposition temperature of ammonium tungstate is above 100°C. Therefore, during the low-temperature dropwise coating reaction, ammonium tungstate is still distributed on the surface of the matrix material in the form of molecular groups, and cannot react with the residual alkali in the form of ionic groups. Therefore, the residual alkali content (carbonate, hydroxide, etc.) in the positive electrode material is increased compared with Example 1, resulting in increased gas production of the positive electrode material during the cycle and increased impedance.

[0234] According to the test data of Example 1 and Example 9, the temperature of the second sintering treatment of the positive electrode material in Example 9 is too low during the preparation process, the V2-V1 value of the prepared positive electrode material is lower than that of Example 1, the coating effect of the surface coating layer of the positive electrode material is deteriorated, the surface residual alkali and impedance of the positive electrode material are increased, the gas production of the positive electrode material is increased, and the expansion rate is also increased.

[0235] According to the test data of Example 1 and Example 12, the amount of deionized water used in the process of preparing the coating solution of the positive electrode material of Example 12 is relatively small, the coating effect of the coating layer on the surface of the positive electrode material is deteriorated, the value of V2-V1 of the prepared positive electrode material is lower than that of Example 1, and the expansion rate and impedance of the battery made of the positive electrode material are increased.

[0236] According to the test data of Example 1 and Comparative Example 1, in the process of continuous spraying of the solution, the material of Comparative Example 1 is prone to local water absorption and agglomeration, which makes the coating effect of the positive electrode material coating layer poor, and the V2-V1 value of the obtained positive electrode material is too low compared with Example 1, and the impedance and cycle expansion rate of the positive electrode material increase. In addition, due to the poor coating effect, the binding ability of the coating material and the positive electrode material is weak, and the inherent defects of the primary particles of the material are not significantly improved, resulting in the particle strength G of Comparative Example 1 being poor. D50 Weaker than Example 1.

[0237] According to the test data of Example 1 and Comparative Example 2, the positive electrode material of Comparative Example 2 is dry-coated during the preparation process, the coating effect of the coating layer on the surface of the positive electrode material is poor, the V2-V1 value of the prepared positive electrode material is too low compared with that of Example 1, the surface residual alkali and gas production of the positive electrode material increase, the impedance of the negative electrode material increases, the cycle expansion rate becomes larger, and the safety performance of the positive electrode material decreases.

[0238] According to the test data of Example 1 and Comparative Example 3, it can be seen that the amount of deionized water added to the positive electrode material of Comparative Example 3 during the preparation of the coating solution is too much. During the coating process, water washing significantly reduces the residual alkali on the surface of the material, but water washing also causes side reactions on the surface of the positive electrode material, making it easy for the layered structure on the surface of the positive electrode material to be transformed into a face-centered cubic structure, and finally into an inactive rock salt phase, thereby causing the impedance of the positive electrode material to continue to increase during the cycle; in addition, the interface stability of the positive electrode material is poor, and it is easy to react with the electrolyte during the cycle, resulting in more gas production.

[0239] also, Figure 2 and Figure 3 The titration curves of the positive electrode materials of Example 1 and Example 7 are respectively, Figure 4 and Figure 5 The titration curves of the positive electrode materials of Comparative Examples 2 and 3 are shown in FIG. Figures 2 to 5 According to the analysis in Table 3, compared with Comparative Examples 1-3: It can be concluded from the V2-V1 value that the positive electrode materials of Examples 1 to 18 have more reasonable doping and coating amounts, which are more conducive to improving the structural stability of the positive electrode materials and reducing the residual alkali in the positive electrode materials; It can be concluded from the dpH / dV value that the elements in the positive electrode materials of Examples 1 to 18 are more evenly distributed and have better structural stability; By controlling the N value within a reasonable range, the test accuracy of the V2-V1 value of Examples 1 to 18 can be guaranteed, which is to say that the above analysis of the V2-V1 value in each embodiment and comparative example is more persuasive. In summary, when the potentiometric titration curve of the positive electrode material satisfies: 2<N≤4, 0.6<V2-V1<2.7, and 0<dpH / dV<10, the processing performance of the positive electrode material is better, and the capacity performance and cycle performance are more excellent.

[0240] from Figure 6 It can be seen that doping and coating have no effect on the crystal structure of the positive electrode material, and the two pairs of split peaks (006) / (012) and (018) / (110) are obvious. 003 / I 104 The peak intensity ratios are all greater than 1.4, indicating that the positive electrode materials prepared in each example have a good layered structure.

[0241] Figure 7This is a particle size distribution diagram of the positive electrode material sample prepared in Example 7, which shows that the positive electrode product prepared in Example 7 has a single-peak particle size distribution.

[0242] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A positive electrode material, characterized in that: The positive electrode material is a nickel-cobalt-lithium composite oxide; the positive electrode material comprises a base material and a coating layer located on at least a portion of the surface of the base material; The positive electrode material is subjected to an acid-base potentiometric titration test using a potentiometric titrator and hydrochloric acid with a concentration of 0.02 mol / L to obtain a curve diagram showing the relationship between the differential value dpH / dV and the consumed volume VmL of the hydrochloric acid, wherein the dpH / dV is a differential value obtained by differentiating the pH value with respect to the consumed volume VmL of the hydrochloric acid; In the relationship curve diagram of the differential value dpH / dV and the consumption volume V mL of the hydrochloric acid, the positive electrode material has a first characteristic peak when the consumption volume of the hydrochloric acid is V1 mL, the positive electrode material has a last characteristic peak when the consumption volume of the hydrochloric acid is V2 mL, and V1 and V2 satisfy the relationship: 0.6<V2-V1<2.

7.

2. The positive electrode material according to claim 1, characterized in that 4<V1<8; and / or, 5<V2<11.

3. The positive electrode material according to claim 2, characterized in that In the relationship curve between the differential value dpH / dV and the consumption volume V of the hydrochloric acid, the positive electrode material has N characteristic peaks in the range of 4 to 11 (excluding 4 and 11) of the consumption volume VmL of the hydrochloric acid, and 2<N≤4.

4. The positive electrode material according to claim 1, characterized in that 0<dpH / dV<10.

5. A positive electrode material, characterized in that The positive electrode material is a nickel-cobalt-lithium composite oxide; the positive electrode material comprises a base material and a coating layer located on at least a portion of the surface of the base material; The positive electrode material was tested by XRD diffractometer, and the diffraction peak intensity of the (003) crystal plane of the positive electrode material was obtained to be I 003 , the diffraction peak intensity of (104) crystal plane is I 104 , and the grain size corresponding to the (104) crystal plane is calculated according to the Scherrer formula as D 104 ; The structural stability coefficient ε of the positive electrode material satisfies: ε=log(D 104 ) / R, 0.90<ε<1.03, where R=I 003 / I 104 .

6. The positive electrode material according to claim 5, characterized in that 45<D 104 <65; and / or, R>1.

6.

7. The positive electrode material according to claim 1 or 5, characterized in that The chemical formula of the positive electrode material is LiNi a Co b Mn c M d Q e O2, wherein 0.8<a<0.98, b<0.2, c<0.2, a+b+c+d+e=1, M is a doping element, Q is a coating element, and the positive electrode material includes at least one of the following characteristics: (1) The doping element M includes at least one of Sr, Ti, Al, Zr, Y, Ba, Mg, Nb, Mo, W and V; (2) The coating element Q includes at least one of S, W, F, P and Mo.

8. The positive electrode material according to claim 1 or 5, characterized in that The positive electrode material includes at least one of the following features: (1) The conductivity of the positive electrode material is greater than 0.03S / cm; (2) The particle hardness G of the positive electrode material D50 >80Mpa,G D90 >50Mpa; (3) The particle hardness G of the positive electrode material D50 >80Mpa,G D90 >50Mpa, and 1≤G D50 / G D90 ≤1.

5.

9. The positive electrode material according to claim 1 or 5, characterized in that: The positive electrode material includes at least one of the following features: (1) The average particle size D of the positive electrode material 50 9μm~12μm; (2) The compaction density of the positive electrode material is greater than 3.0 g / cm 3 ; (3) The pH value of the positive electrode material is 11 to 12; (4) The specific surface area of ​​the positive electrode material is greater than 0.2 m 2 / g; (5) The positive electrode material tap density is greater than 2.0 g / cm 3 .

10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium ion battery positive pole material with core-shell structure, preparation method thereof, positive pole sheet, lithium ion battery and application of lithium ion battery

    CN110660978A

  • Method for testing content of residual alkali in coated and modified positive electrode material and application thereof

    CN111948335A

  • Composite positive electrode material, preparation method thereof and lithium ion battery

    CN114614006A

  • Anode active material for lithium secondary battery, method for preparing same, and lithium secondary battery comprising same

    CN116544403A

  • High-nickel ternary positive electrode material, preparation method thereof and lithium ion battery

    CN117334860A